Resurfacing of the humeral head: An analysis of the bone stock and osseous integration under the implant. Issue 9 (14th April 2015) - Schmidutz, Florian; Sprecher, Christoph M.; Milz, Stefan; Gohlke, Frank; Hertel, Ralph; Braunstein, Volker
ABSTRACT Cementless‐surface‐replacement‐arthroplasty (CSRA) of the shoulder aims for functional joint restoration with minimal bone loss. Good clinical results have been reported, but due to the radiopaque metal shell no data is available on the structure, osseous integration, and bone stock under the implant. 14 hemi‐CSRAs (4 manufacturers) with two geometries (crown [n = 7]/ stem [n = 7] fixation) were retrieved from patients undergoing revision due to glenoidal erosion. Histological sections cutting through the implant centre and bone were analysed. Quantitative histomorphometry evaluated the bone‐implant‐contact and compared the bone‐area to native humeral retrievals (n = 7). The bone‐implant‐interface was further assessed by scanning‐electron‐microscopy (SEM) and energy‐dispersive‐x‐ray (EDX). Qualitative histology revealed a reduced and inhomogeneous bone stock. Obvious signs of stress shielding were observed with bone predominantly visible at the stem and implant rim. Quantitative histomorphometry confirmed the significantly reduced bone‐area (9.2 ± 3.9% [crown 9.9 ± 4.3%, stem 8.6 ± 3.6%]) compared to native humeri (21.2 ± 9.1%; p < 0.05). Bone‐implant‐contact was 20.5 ± 5.8% (crown 21.8 ± 6.2%, stem 19.2 ± 5.6%) which was confirmed by SEM and EDX. Altogether, CRSA shows satisfactory bone ingrowth at the interface suggesting sufficient primary stability to allow osseous integration. However, clear signs of stress shielding with an inhomogeneous and reduced bone stock were observed. The impact on the long‐term‐results is unclear requiring further investigation. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1382–1390, 2015.